2010
DOI: 10.1007/s10803-010-1114-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prenatal, Obstetric and Neonatal Factors in the Development of Autism

Abstract: We conducted a linked database cohort study of infants born between 1990 and 2002 in Nova Scotia, Canada. Diagnoses of autism were identified from administrative databases with relevant diagnostic information to 2005. A factor representing genetic susceptibility was defined as having an affected sibling or a mother with a history of a psychiatric or neurologic condition. Among 129,733 children, there were 924 children with an autism diagnosis. The results suggest that among those with low genetic susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
224
1
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(260 citation statements)
references
References 42 publications
(54 reference statements)
21
224
1
13
Order By: Relevance
“…6 However, whether and how the effects of GDM and PGDM differ is still debatable. Although the 2 studies differentiating PGDM and GDM in the meta-analysis both reported larger odds ratios (ORs) for PGDM than GDM, 15,16 Xiang et al 17 found that only GDM diagnosed before 26 weeks, but not GDM diagnosed 7…”
Section: Discussionmentioning
confidence: 99%
“…6 However, whether and how the effects of GDM and PGDM differ is still debatable. Although the 2 studies differentiating PGDM and GDM in the meta-analysis both reported larger odds ratios (ORs) for PGDM than GDM, 15,16 Xiang et al 17 found that only GDM diagnosed before 26 weeks, but not GDM diagnosed 7…”
Section: Discussionmentioning
confidence: 99%
“…106,109,139,140 Two 141,142 of three cohort studies [141][142][143] found a significant association between either prepregnancy weight, pregnancy weight gain or early-life obesity and ASD. A 2009 metaanalysis found a positive association between maternal gestational diabetes and ASD.…”
Section: Parental Agementioning
confidence: 99%
“…A 2009 metaanalysis found a positive association between maternal gestational diabetes and ASD. 100 Since then, there have been conflicting findings, 102,124,139,141,144,145 although some of these studies did not differentiate between prepregnancy and gestational diabetes.…”
Section: Parental Agementioning
confidence: 99%
“…A total of 12 studies (6 cohort, 5 cross-sectional, and 1 case-control), including 1 334 569 children, met the inclusion criteria. [28][29][30][31][32][33][34][35][36][37][38][39] The individual characteristics and main findings of the studies included in the systematic review are shown in Table 1. Seven studies provided data on ASD, 28 …”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Three studies showed a U-shaped association between IPI and the risk of ASD. 31,33,34 Six studies found a significant association between short IPIs (<12 months, 30,31,33 <18 months, 29 <24 months, 34 and <36 months 28 ) and increased risk of ASD.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%